2013
DOI: 10.1061/(asce)st.1943-541x.0000679
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of a Chevron Concentrically Braced Frame

Abstract: Abstract:Large-scale shake table tests were conducted at E-Defense, Japan, to examine the 4 dynamic response of a steel concentrically braced frame. The specimen was a single-bay, single-5 story frame with a pair of square-HSS braces placed in a chevron arrangement. The gusset plates 6 connecting the brace to the framing elements were provided with an elliptic fold line to 7 accommodate out-of-plane rotation of the brace in compression. The specimen was subjected 8 repeatedly to a unidirectional ground motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…Figure 1 suggests that there is a strong correlation between the DSFs and story-based EDPs. Same findings hold true for the rest of the shake table experiments that were investigated [24][25][26][27]. …”
Section: Wavelet-based Damage-sensitive Features For Structural Damagmentioning
confidence: 68%
See 1 more Smart Citation
“…Figure 1 suggests that there is a strong correlation between the DSFs and story-based EDPs. Same findings hold true for the rest of the shake table experiments that were investigated [24][25][26][27]. …”
Section: Wavelet-based Damage-sensitive Features For Structural Damagmentioning
confidence: 68%
“…Hwang and Lignos [22] conducted further validations on the potential use of wavelet-based DSFs for structural damage identifications based on full-scale shake table experiments on steel frame buildings with steel MRFs [24,25] and concentrically braced frames [26,27]. They found that the mapping of a DSF value to a story-based EDP is possible.…”
Section: Wavelet-based Damage-sensitive Features For Structural Damagmentioning
confidence: 99%
“…In another experimental study, Bubela et al [21] examined incorporating vertical slotted connection in steel chevron braced frame to prevent vertical load transfer to beam through full-scale quasi-static cyclic tests of two specimens. Dynamic response of steel CBF with chevron arrangement and elliptical fold line in gusset plate connection was performed through test on large-scale shaking table [22]. In this study, excellent behavior of connection was observed and yielding in the middle of beam did occur as predicted in monotonic analysis.…”
Section: -Introductionmentioning
confidence: 87%
“…The white noise test indicates that the equivalent viscous damping ratio is 443 fairy high (i.e., it ranges between 5.3% and 6.6%) regardless of the employed system identification technique. This is 444 due to the friction of the test bed to the sliders (Okazaki et al 2011(Okazaki et al , 2013a). However, this issue diminishes after the 445 14% of the unscaled JR Takatori record because the inertia forces become larger than the corresponding friction forces.…”
Section: Equivalent Damping Ratio and Mode Shapes As Damage Indicators 408mentioning
confidence: 99%